2005
DOI: 10.1002/jcc.20217
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the reaction mechanism of the methyl radical with nitrogen oxides

Abstract: The radical-molecule reaction mechanism of CH3 with NOx (x = 1, 2) has been explored theoretically at the B3LYP/6-311Gd,p and MC-QCISD (single-point) levels of theory. For the singlet potential energy surface (PES) of the CH3 + NO2 reaction, it is found that the carbon to middle nitrogen attack between CH3 and NO2 can form energy-rich adduct a (H3CNO2) with no barrier followed by isomerization to b1 (CH3ONO-trans), which can easily convert to b2 (CH3ONO-cis). Subsequently, starting from b (b1, b2), the most fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Nitric oxide (NO) as a combustion product can react with several hydrocarbon radicals. Among these radicals, propargyl radical (C 3 H 3 ) has been proposed as critical intermediates in hydrocarbon reaction systems pertinent to both low temperatures of planetary atmospheres and high temperatures of combustion systems, since it has been widely proposed to play a major role in the formation of the aromatic rings via the self-reaction in the combustion system and can accumulate in relatively high concentrations in flame because of its resonantly stabilized structure. For the propargyl radical reactions, both of the resonant structures acetylenic hybrid (HCC–CH 2 ) and allenic hybrid (HCCCH 2 ) were taken into consideration, such as C 3 H 3 reaction with O ( 3 P), O 2 , , C ( 3 Pj), CH 3 , allyl (C 3 H 5 ), benzyl (C 7 H 7 ) . The reaction between C 3 H 3 and NO could have an impact on several aspects of combustion chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO) as a combustion product can react with several hydrocarbon radicals. Among these radicals, propargyl radical (C 3 H 3 ) has been proposed as critical intermediates in hydrocarbon reaction systems pertinent to both low temperatures of planetary atmospheres and high temperatures of combustion systems, since it has been widely proposed to play a major role in the formation of the aromatic rings via the self-reaction in the combustion system and can accumulate in relatively high concentrations in flame because of its resonantly stabilized structure. For the propargyl radical reactions, both of the resonant structures acetylenic hybrid (HCC–CH 2 ) and allenic hybrid (HCCCH 2 ) were taken into consideration, such as C 3 H 3 reaction with O ( 3 P), O 2 , , C ( 3 Pj), CH 3 , allyl (C 3 H 5 ), benzyl (C 7 H 7 ) . The reaction between C 3 H 3 and NO could have an impact on several aspects of combustion chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude and the negative temperature dependency of the measured rate coefficients suggest that these radical-radical reactions proceed without any notable energy barrier to form a collision complex, for example via N-or O-atom attack of the NO 2 on the radical center. The potential energy surface of the CH 3 + NO 2 reaction given by Biggs et al 34 and Yamaguchi et al 35 for various reaction pathways include both N-and O-atom attack of the NO 2 on the carbon atom, while Zhang et al 36 have obtained interaction only between N atom of the NO 2 and the C atom of the methyl radical. The energized methyl nitrite (CH 3 ONO) can then decompose to bimolecular products via transition state(s) located energetically below the reactants, while energized nitromethane (CH 3 NO 2 ) dissociates back to the reactants, collision stabilizes, or possibly overcomes high barrier(s) for rearrangements.…”
Section: Resultsmentioning
confidence: 99%
“…The potential energy surface of the CH 3 + NO 2 reaction given by Biggs et al . and Yamaguchi et al for various reaction pathways include both N- and O-atom attack of the NO 2 on the carbon atom, while Zhang et al have obtained interaction only between N atom of the NO 2 and the C atom of the methyl radical. The energized methyl nitrite (CH 3 ONO) can then decompose to bimolecular products via transition state(s) located energetically below the reactants, while energized nitromethane (CH 3 NO 2 ) dissociates back to the reactants, collision stabilizes, or possibly overcomes high barrier(s) for rearrangements. This is also consistent with the recent studies of Wollenhaupt et al and Kukui et al on the CH 3 + NO 2 reaction, where both bimolecular and termolecular reaction channels have been observed.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a detailed theoretical investigation on the potential energy surface for CH 2 OH reaction with NO 2 had been carried 27 The possible reaction pathways are summarized as For distinction purposes, the calculated pathways for the CH 3 + NO 2 reaction are shown in italics. We found that P 1 (CH 3 O + NO) and P 2 (CH 2 O + HNO) are the most favorable products with comparable yields, whereas P 3 (CH 2 O + HON) is the least competitive product.…”
Section: Initial Associationmentioning
confidence: 99%